2018
DOI: 10.1155/2018/1219367
|View full text |Cite
|
Sign up to set email alerts
|

Selected Enzyme Inhibitory Effects of Euphorbia characias Extracts

Abstract: Extracts of aerial part of Euphorbia characias were examined to check potential inhibitors for three selected enzymes involved in several metabolic disorders. Water and ethanol extracts from leaves and flowers showed in vitro inhibitory activity toward α-amylase, α-glucosidase, and xanthine oxidase. IC50 values were calculated for all the extracts and the ethanolic extracts were found to exert the best effect. In particular, for the α-glucosidase activity, the extracts resulted to be 100-fold more active than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…Based on our results, the extract of T. cochinchinensis stem bark was weakly active in inhibiting XO activity as compared to allopurinol (p<0.05) (Figure 3). Previous studies have reported a similar trend of XO inhibition by Euphorbiaceae plants, such as Euphorbia characias, E. formosana, and E. hirta (Fais et al, 2018;Chen et al, 2009;Bangou et al, 2011). Nonetheless, the ethyl acetate and methanol fractions of this plant exhibited a promising XO inhibitory activity with inhibitions of 80.5% in FEa and 67.8% in FMe, respectively at a dose of 100 μg/mL.…”
Section: Resultssupporting
confidence: 57%
“…Based on our results, the extract of T. cochinchinensis stem bark was weakly active in inhibiting XO activity as compared to allopurinol (p<0.05) (Figure 3). Previous studies have reported a similar trend of XO inhibition by Euphorbiaceae plants, such as Euphorbia characias, E. formosana, and E. hirta (Fais et al, 2018;Chen et al, 2009;Bangou et al, 2011). Nonetheless, the ethyl acetate and methanol fractions of this plant exhibited a promising XO inhibitory activity with inhibitions of 80.5% in FEa and 67.8% in FMe, respectively at a dose of 100 μg/mL.…”
Section: Resultssupporting
confidence: 57%
“…The cellular ROS levels were determined with the DCFH-DA method [ 25 ]. HaCaT cells were treated with various concentrations of MEG (0–50 µg/mL) for 24 h. Then, the cells were incubated with DCFH-DA (10 µM) at 37 °C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…XO activity was measured according to the method previously reported. 5 The reaction mixture contained 879 mL of 100 mM phosphate buffer pH 7.5, 50 mL of an aqueous solution of XO (0.5 U mL À1 ) and 10 mL of the extract sample solution or the control sample solution. Aer mixing, 61 mL of 0.82 mM xanthine solution was added, and the enzyme activity was determined at 295 nm for 3 min at 25 C. Allopurinol was used as the standard XO inhibitor.…”
Section: Xanthine Oxidase Assaymentioning
confidence: 99%
“…1,2 Fruits or underutilized fruit species are receiving more attention, as they contain different phytochemicals that manifest many biological activities, 3 including the ability to inhibit several enzymatic targets. 4,5 Moreover, compared to metabolites in the edible portion of fruits, those present in seeds have an added value and good commercial potential as promising phytochemicals/antioxidants for use in food. 6 The palm family includes a range of plant species with wide application in human food, some of which may also be of pharmacological interest.…”
Section: Introductionmentioning
confidence: 99%